Identifying Limitations in End-to-End Testing: A Systematic Review of Coverage Analysis Techniques - Zendeli, Blerand; Luma, Artan; Selimi, Besnik; Rexha, Blerim (International Congress on Human-Computer Interaction, Optimization and Robotic Applications (Online), 2025)
End-to-end (E2E) testing plays a crucial role in ensuring the seamless functionality of modern software systems by validating entire workflows across user interfaces, backend services, and integrated components. As software architectures evolve with dynamic web applications, event-driven interactions, and microservices, traditional E2E testing methodologies face significant challenges. Asynchronous workflows, dynamically generated content, and the increasing reliance on Continuous Integration and Continuous Deployment (CI/CD) pipelines introduce new complexities that demand innovative testing solutions.This paper presents a systematic literature review to critically examine existing E2E testing frameworks, with a specific focus on test coverage metrics, event-driven architectures, and automation strategies. By analyzing sixteen peer-reviewed studies, we identify key advancements, including mutation analysis, automation pipelines, and microservices testing approaches. However, critical limitations persist, such as the inability to adequately handle uninvoked event listeners, insufficient support for dynamic and asynchronous interactions, and challenges in integrating testing frameworks with modern CI/CD pipelines.Our findings underscore the need for a dynamic evaluation framework that enhances existing methodologies by introducing comprehensive event listener analysis, improved coverage metrics, and adaptable mechanisms for dynamic workflows. By bridging these gaps, we aim to refine E2E testing strategies, ensuring greater reliability, scalability, and effectiveness in software quality assurance.The insights from this study provide a roadmap for future research and practical implementations of E2E testing, advocating for more robust, automation-friendly, and context-aware testing methodologies. As software complexity grows, continuous advancements in E2E testing will be imperative to maintain software quality in an increasingly agile and fast-paced development environment.